Practice Interest and Readiness of Community Pharmacists towards Community Pharmacists’ Roles Development - Sangkar, Pimolsri; Hongsamoot, Duangtip (Journal of Health Science of Thailand, 2018)
Development of the professional pharmacists’ roles tended to focus on the practice of pharmaceutical care, whereas community pharmacists have been lacking. This survey research was aimed at studying the attitudes of community pharmacists towards their professional role development. The data was collected by posting self - completed questionnaires with a five-point rating scale (1-5) representing degree of agreement to 2,820 community pharmacists throughout Thailand from February to April 2008. Five hundred and twenty-seven questionnaires (20%) were returned. The data was analyzed using frequency, percentage, mean, standard deviation and Mann-Whitney U test. The top two community pharmacists’ roles currently provided were selecting appropriate medicine for minor illness and storage medicine to maintain good quality with the mean score of 4.61, SD 0.61 and 4.52, SD 0.64 respectively (total score of 5). In term of pharmaceutical care activities, for example, patient drug profile preparing, prescription refilling, patient referring, the study showed that community pharmacists were active at a low level. Whereas the mean score on provision of home medicine reviews was at the lowest level (1.21, SD 0.63). When considering the interest and readiness to provide pharmaceutical care activities, the mean scores of both issues were at the high level. In comparison, the interest to provide pharmaceutical care activities between accredited and general community pharmacies, the mean scores of accredited pharmacies were significantly higher than that of the general pharmacies with most activities (p<0.05), except prescription filling activities (p 0.068). Regarding the readiness to provide pharmaceutical care activities, the study found that the mean scores of accredited pharmacies were significantly higher than that of the general pharmacies in all activities (p<0.05). Technical and material supports were needed to encourage community pharmacies to practice pharmaceutical care activities. Pharmacists recommended that should not have been limited number of pharmacies but focus should have been more on quality of pharmacies. The finding of this study revealed that pharmaceutical care activities were practiced in the community pharmacies at the low level and unclear. However community pharmacists were interested and ready to practice pharmaceutical care at high and higher level in case of accredited pharmacies. Therefore, the integration community pharmacists into the health care team and participation of patients drug use in the system should be supported.